Paddy straw collector-cum-chopper for in situ paddy straw management: A sustainable approach - Mohd. Muzamil; Indra Mani; Sehreen Rasool; Livleen Shukla; Shyam Nath (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The study was devoted to conceptualize, develop and evaluate a collector-cum-chopper for in situ paddy straw degradation at the farmer’s field level. The intention was to increase the amount of straw cut at size below 5 cm for nutrient recycling.Method A paddy straw collector-cum-chopper comprised of three sub-systems i.e. straw collection and conveying unit, straw chopping device and discharging mechanism was designed and developed. The performance evaluation, economic assessment of paddy straw collector-cum-chopper and fertility status of soil was recorded.Results The results revealed that operating the machine at 40% moisture content, forward speed 3 kmph and 40 cm height of cut resulted into percentage of paddy straw <5 cm, 5-10 cm, 10-15 cm and > 15 cm as 63.5 %, 8.12 %, 6.44 % and 17.92 percent. At such a condition, it consumed 5.78 lh-1, 7.82 kWh-ton-1 energy at 2.06 tonnesh-1 productivity.  The operating cost was Rs.694.6 h-1, break-even point 556 hours per annum, annual utility 1146 tonnes, pay-back period 1 year and unit cost of paddy straw chopping as Rs.58.44 per tonne. The mixing of the treated paddy straw with the soil bolstered NPK and organic carbon by 64.61%, 48.36%%, 74.32% and 54.54% with respect to 38.37%, 34.91%, 38.69%, 43.33% treated paddy straw kept above the soil.Conclusion The study provides an opportunity to bolster nutrient content of the soil, restrict the dependence on hazardous chemical fertilizers and protect the environment.